Something about etiology and prophylaxis of insanity on purpose statistical movement "Insane Hospice Lima" - Delgado, Honorio (1918)
The statistics resulting from the array and accurate facts, offer the study of the elements involved in the complicated process of psychiatric phenomena. solid handle for searching the interlocking who binds their determinants. The application of this approach to mental medicine is not, moreover, but a partial manifestation of his value as a tool for assessing the reality within the scientific canons. So we believe necessary and appropriate to outline some comments on the figures supplied us compare the figures contained in the 1896 and 1916 statistics, to derive numerical variants alienated held at the Hospice of Insanos Lima, take their etiology as current conditions - that the etiologic in other periods of our history factors have been brilliantly treated by our master the Dr.HERMILIO VALDIZAN - etiology take on current conditions and outline the most appropriate prophylactic attitude in harmony with the teachings of hygiene mental and the needs of our psicosanitario future.